Performance evaluation of hydraulic field test rig - Wan Nik, W.B.; Zulkifli, F.; Mohamad Ayob , Ahmad Faisal; Olanrewaju, Sulaiman O.; Rahman, Md. Mokhlesur (Elsevier, 2013)
Development of environmental friendly hydraulic fluid has a major influence on ecologically benign environment. This future type of oil should be non-toxic, biodegradable and ecological benign. Subsequently, it becomes crucial to recognize the sustainability of such oil in maintaining a high system performance which resulting in tremendous contribution towards machinery technology. Furthermore, the development of methods to evaluate the actual performance of hydraulic fluid has been of great interest. In this project a hydraulic test rig was built to conduct endurance test where it can be operated continuously with several safety features. The rig was used to test the oil and other stringent parameters, running for nearly 1000 hours. Major factors in the decrease of mechanical efficiency are thermal heat, friction, aging behaviour and contamination of the plant oil. Explained in this paper are the features of the hydraulic system built to evaluate the performance of plant oils.